2019
DOI: 10.1109/access.2019.2900249
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Segmentation Optimized by Physical Information for Gridding of Microarray Images

Abstract: As one of the great advances in modern technology, the microarray is widely used in many fields, including biomedical research, clinical diagnosis, and so on. Evidently, in order to extract the intensity of fluorescence bio-probes accurately, we need to pay special attention to the gridding of microarray at first. To solve the poor effect of the traditional Otsu method for microarray gridding, an innovative algorithm of Otsu optimized by multilevel thresholds is proposed to improve the accuracy and effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…[5]. The activation of PI3K-Akt signaling pathway is closely related to colorectal cancer metastasis and poor prognosis [6][7]. Research shows [8] that a deregulated PI3K-AKT signaling pathway in CRC patients, which might serve as therapeutic target(s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5]. The activation of PI3K-Akt signaling pathway is closely related to colorectal cancer metastasis and poor prognosis [6][7]. Research shows [8] that a deregulated PI3K-AKT signaling pathway in CRC patients, which might serve as therapeutic target(s).…”
Section: Discussionmentioning
confidence: 99%
“…Through integrated bioinformatics analysis, 10 hub genes were identi ed, including MCM3,MCM7, BUB1B,AUPKA,TPX2, TTK,FEN1, cyclin B1(CCNB1),cyclin A2(CCNA2) and KIF4A with a high degree of connectivity.Among them, MCM3 and MCM7 belong to the MCMs family, and their biological functions are primarily involved in the DNA replication [2].Multiple previous studies have demonstrated that minichromosome maintenance(MCM) protein additionally serve a role in the occurrence and development of varies malignancies [3][4][5].The MCM participates in DNA synthesis [6] and can be used as a biomarker of oral squamous cell carcinoma [7], melanoma [8], glioma [9] and colon cancer [10]. In this study, the KEGG pathway showed that the DEGs were mainly involved in the cell cycle and DNA replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accidental microarray image rotation is detected and corrected using Radon transform, as reported in [6] . As described in [7], spot group detection is performed using an approach based on mathematical morphology, which identifies the groups of spots using an image closing procedure. The aforementioned preprocessing techniques transformed the original image I into several I p images, each containing one group of spots.…”
Section: A Preprocessingmentioning
confidence: 99%
“…As reported in [4], [5], automatic grid alignment is performed using a SVM based approach, whereas based on a spot selection step, a set of grid lines are placed over the image in order to separate each pair of consecutive rows and columns. Unsupervised grid alignment methods for microarray images have been also proposed [6], [7] based on the use of optimal multilevel thresholding followed by a refinement procedure to find the positions of the sub-grids in the image and the positions of the spots in each detected sub-grid. For the segmentation of microarray spots, adaptive pixel clustering techniques were used in [8], [9], [10] .…”
Section: Introductionmentioning
confidence: 99%